Analysis of the Symbolic Meaning of the Ratib Ritual in the Tradition of Tolak Bala in Gedung Muara Village, Seruway District, Aceh Tamiang Regency - Rifna Dayanti; Safriandi Safriandi; Rasyimah Rasyimah (SAINTIS Publishing, 2025)
This study aims to analyze the symbolic meanings embedded in the ratib berjalan ritual within the tolak bala tradition in Gedung Biara Village, Seruway Sub-district, Aceh Tamiang Regency, as well as the local wisdom values underlying it. The ratib berjalan tradition is one of the tolak bala rituals that is still preserved by the community of Gedung Biara Village. This ritual is held annually in the month of Safar, with the purpose of driving away evil spirits and seeking protection from misfortunes. The semiotic approach of Charles Sanders Peirce is used to interpret symbols such as white robes, whips (regis), torches, flags inscribed with Lailahaillallah, and various taboos observed during the ritual. This research uses a qualitative method with data collected through observation, interviews, and documentation. The results show that the eight symbols in the ratib berjalan ritual possess profound philosophical and spiritual meanings such as purity, protection, and togetherness.